1996
DOI: 10.1055/s-2008-1066490
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Patches Used to Close Congenital Diaphragmatic Defects Behave Well: A Long-Term Follow-Up Study

Abstract: To answer the question of what happens with time with prosthetic patches inserted to close a congenital diaphragmatic hernia, a retrospective study concerning the period 1982-1993 was undertaken. Thirty children received patch reconstruction. None of these patients had agenesis of the diaphragm. Early patch-related complications did not occur, but seven patients died shortly after the operation as a result of lung hypoplasia. Twenty-three patients with patch reconstruction of the diaphragm survived and were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 1 publication
1
33
0
Order By: Relevance
“…This may reflect the fact that men are more likely to sustain mild to moderate trauma at a younger age. Whereas our review found that 62% of the patients were female, it is reported that the prevalence among infants is equal between the sexes [36].…”
Section: Discussionmentioning
confidence: 86%
“…This may reflect the fact that men are more likely to sustain mild to moderate trauma at a younger age. Whereas our review found that 62% of the patients were female, it is reported that the prevalence among infants is equal between the sexes [36].…”
Section: Discussionmentioning
confidence: 86%
“…11,25 Surgical treatment of congenital abnormalities is often complicated by insufficient available tissue at the time of repair, resulting in the use of synthetic materials and a corresponding high morbidity rate. [26][27][28][29][30] Alternatively, broad potential for differentiation and high proliferation rates make AFSC well suited for use in regenerative medicine therapies such as engineered skeletal/cardiac muscles, tendons, heart valves, and blood vessels. 11,17,[31][32][33][34][35] This study confirms our previous work on the capacity for VEGF-mediated differentiation of c-kit + AFSC into endothelial-like cells, 14 as well as illustrates the vasculogenic and perivasculogenic potential of AFSC within a threedimensional fibrin/PEG scaffold in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by de Kort and Bax, only 1 of 30 children undergoing prosthetic patch repair of CDH experienced recurrence. However, none of the patients in that series had diaphragmatic agenesis, and most of the diaphragmatic defects were described as small or moderate [6]. Moss et al [7] reported a different experience with the GT patch.…”
Section: Discussionmentioning
confidence: 96%
“…The use of the Gore-Tex (GT) patch seems to vary among different centers and comparison of results is not clear. Some may use patches very liberally, whereas others view reconstruction with foreign material as a last resort [6][7][8]. However, there are long-term complications associated with the use of synthetic patches.…”
Section: Introductionmentioning
confidence: 97%